PENGARUH WORK FROM HOME, STRES KERJA, DAN PELATIHAN KERJA TERHADAP KINERJA PEGAWAI PADA SMK WIDYA NUSANTARA BEKASI: Pengaruh Work From Home, Stres Kerja, dan Pelatihan Kerja Terhadap Kinerja Pegawai Pada SMK Widya Nusantara Bekasi - Atika Febriyanti; Bayu Seno Pitoyo (Fakultas Ekonomi Dan Bisnis Universitas Bhayangkara Jakarta Raya, 2023)
Effect of Work From Home, Job Stress, and Job Training on Employee Performance at SMK Widya Nusantara Bekasi. This study was conducted to determine whether there is an effect of Work From Home, job stress, and job training on employee performance at SMK Widya Nusantara Bekasi. The sampling technique used is total sampling where the number of samples is 49 respondents. Data collection techniques by distributing questionnaires to 49 employees of SMK Widya Nusantara Bekasi. The design used in this study is hypothesis testing (SEM) – SmartPLS 3.0. Based on the results of the analysis that has been done that Partially Work From Home does not have a significant effect on employee performance, Work Stress partially does not have a significant effect on employee performance, and job training has a significant effect on employee performance. Then simultaneously the variables Work From Home, Job Stress, and Job Training have a positive and significant effect on employee performance at SMK Widya Nusantara Bekasi.